Siti Walidah and her contribution to Islamic women's movement: Gadamer’s fusion of horizon - Santosa, Budi Tri; Mutmainnah, Yulia; Satwika, Rakindra Cahya (Universitas Dian Nuswantoro, 2024)
This research focuses on Siti Walidah and her preaching in Java in the film script of Nyai Ahmad Dahlan. By focusing on Siti Walidah, this research has several objectives., which are the fusion of horizons towards Siti Walidah to unveil interesting insights into merging cultural boundaries, investigating the transformation of traditional practices and beliefs by fusing horizons between different cultures, and exploring the experiences of Siti Walidah, who exemplifies the intermingling of Indonesian and Western cultures. This research is a qualitative study that uses a hermeneutic approach. In methodological principles, Gadamer's hermeneutics aligns with qualitative research, which aims to find a deep understanding that requires qualitative interpretation. The data source in this research is a literary work of a film script entitled Nyai Ahmad Dahlan (2017) by looking for variables or data from Siti Walidah's manuscript as the object of research on theological humanism in Javanese society in the pre-independence era through several stages: determining research questions, selecting research objects, reviewing data, data categorization, data validation, data analysis, and interpretation. The research findings on the fusion of horizons towards Siti Walidah unveil interesting insights into merging cultural boundaries. The research reveals that the fusion of horizons contributes to a multifaceted identity, allowing Siti Walidah to navigate and embrace diverse cultural perspectives. Moreover, it highlights the positive impact of cultural fusion on personal growth and the development of a unique identity that transcends boundaries. Overall, this research sheds light on the potential benefits and challenges of merging cultures.